Modern civilization approach to understanding the essence of terrorism - Ященко, Олександр Григорович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
The article exposes maintenance of civilization approach to comprehension essence of terrorism, what is a new in criminal law